Effects of Nitrogen Sources on Selected Biochemical Properties of Oryza Sativa L. Cultivars - Yap, Wai Sum (2006)
Fifteen recommended rice cultivars were used in this experiment. They were Setanjung, Muda, MR 84, RU 2242-1-1, IR 64, MR 185, MR 151, MR 159, MR 167, MRQ 34, MR 207, MR 209, MR 211, MR 219 and MR 220. Leaves of three-week old seedlings were analyzed for nitrogen assimilating enzymes, namely nitrate reductase (NR), nitrite reductase (NiR), glutamine synthetase (GS), glutamate synthase (GOGAT) and glutamate dehydrogenase (GDH) activities to evaluate the assimilation of N supply whereas ribulose 1,5-bisphosphate carboxylase/oxygenase (Rubisco) activity was use as an indicator for photosynthesis. The end products of N and C metabolism such as chlorophyll, soluble protein, fresh weight, soluble carbohydrates and starch contents were also analyzed. These biochemical evaluation were carried out in three different growth medium known as ‘control ~ without nitrogen sources’, ‘NO3 - containing medium’ and ‘NH4 + containing medium’ to determine the effect of different N sources. Treatments were laid out in split-plots in a randomized complete block design with N treatment as the main plot and cultivars as the subplot. In the study obtained, the addition of external N sources did not help in accelerating the activities of N assimilating enzymes (NR, NiR, GS, GOGAT and GDH) as well as Rubisco when compared to control medium. In the leaves of three-week old seedlings, NR, NiR, GS and Rubisco activities were negatively related with the availability of N sources (-88%, -28%, -22% and -13%, respectively). GOGAT activity was demonstrated not to be influenced by the addition of N sources (no significant different) whereas GDH activity was higher in control (+51%) and NH4 + (+20%) containing medium as compared to NO3 -. In investigation of the effects of different nitrogen sources on selected N and C metabolites, positive correlation was observed. The increment of nearly 40% under nitrate supply and 62% in ammonium of the soluble protein content was seen with the external addition of N. Similarly, there was also an increased in the fresh weight (FW) content of nearly 0.8-fold in NO3 - grown plants to 0.2-fold in NH4 + fed plants when different N sources were applied (the increased in ammonium supply was not statistically significant in comparison with control). This lower FW content under ammonium supply could be the consequences of the slight chlorosis observed in the leaves tissue. In contrast, chlorophyll content happened to be lower in both NO3 - and NH4 + containing medium, with a reduction of 30% and 14%, respectively. Soluble carbohydrates content was slightly higher under nitrate supply than in ammonium whereas the control medium was found to possess higher starch content. Lower starch content in both medium (NO3 - and NH4 +) could possibly relate to higher nitrogen use efficiency which resulted in an increase of soluble protein and FW contents. Apparently, the antioxidative property of ascorbic acid content was significantly higher in both control and NH4 + containing medium, whereas glutathione reductase (GR) activity was highest under ammonium supply. Cultivars as the subplot were found to demonstrate high significant evidence (P < 0.001) and were in consistency among the entire biochemical analyses, indicating genetic materials (15 rice cultivars) being one of the influential factor in regulating the outcome of the biochemical results obtained.